On-line Signature Verification based on Pen Inclination and Pressure Information - Jungpil Shin; Tetsuya Takanashi (International Journal of Electrical and Computer Engineering (IJECE), 2012)
In this paper, the features that have personal characteristic using pen inclination and pressure information are discussed. Forging a pen inclination and pressure information is difficult because it is not visible. Four features using invisible information are proposed and their characteristics are discussed. Proposed features calculated by physical vector analysis are verified by SVC2004 database using DP matching algorithm. As a result, the new feature named Down improves the recognition rate and reliability. Average of correct verification rate is 94.57 % and variance is 0.667.DOI:http://dx.doi.org/10.11591/ijece.v2i4.474